2022
DOI: 10.1002/cpdd.1140
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐Drug Interaction Studies to Evaluate the Effect of Inhibition of UGT1A1 and CYP3A4 and Induction of CYP3A4 on the Pharmacokinetics of Tropifexor in Healthy Subjects

Abstract: Tropifexor, a farnesoid X receptor agonist, is currently under clinical development for the treatment of nonalcoholic steatohepatitis. Tropifexor undergoes glucuronidation by uridine 5′‐diphosphoglucuronosyltransferase (UGT) 1A1 and oxidation by cytochrome P450 (CYP) 3A4, as reported in in vitro studies. Here, we report the results from 2 drug‐drug interaction studies. Study 1 enrolled 20 healthy subjects to investigate the effect of the UGT1A1 inhibitor atazanavir (ATZ) on tropifexor pharmacokinetics (PK). St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…A clinical study in healthy individuals revealed that the inhibitory effect of itraconazole on CYP3A4 resulted in the increased systemic exposure of tropifexor (Chen et al. 2022 ). The inhibition of CYP3A4 by physcion was also observed in this study, which was non-competitive.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical study in healthy individuals revealed that the inhibitory effect of itraconazole on CYP3A4 resulted in the increased systemic exposure of tropifexor (Chen et al. 2022 ). The inhibition of CYP3A4 by physcion was also observed in this study, which was non-competitive.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the elimination of this drug in the form of glucuronides, incompatibilities of lumateperone with substances that are inhibitors of UGT enzymes are also important. The drugs and food components with which lumateperone interacts and their description are shown in Table 1 (Intra-Cellular Therapies, 2019; Hussar, 2021; Chen et al, 2022).…”
Section: { Lumateperone -Interactions With Other Drugsmentioning
confidence: 99%
“…Interakcje lumateperonu z lekami i składnikami pożywienia (Intra-Cellular Therapies, 2019; Hussar, 2021;Chen et al, 2022) …”
unclassified
“… 1 , 10 According to recently published research, pre‐dosing of rifampin at 600 mg QD varied from 7 to 14 days in NME DDI studies. 7 , 12 , 13 To provide further evidence for standardizing the design of clinical DDI studies and reducing variability, we conducted this real‐world clinical trial to compare the two most widely used rifampin dosing regimens (600 mg QD for 7 days vs. 600 mg QD for 14 days) in DDI studies.…”
Section: Introductionmentioning
confidence: 99%